Vacuum cleaners and washing machines display - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows some men and women around displays for vacuum cleaners and washing machines. A sign reads, " Phone SJ 1365, Good Housekeeping Shop, 235 S. First St." Material from a large tent appears above and behind this scene.